MicroRNA Profiles in Normotensive and Hypertensive South African Individuals - Matshazi, Don M.; Weale, Cecil J.; Erasmus, Rajiv T.; Kengne, Andre P.; Davids, Saarah F. G.; Raghubeer, Shanel; Hector, Stanton; Davison, Glenda M.; Matsha, Tandi E. (Frontiers in Cardiovascular Medicine, 2021)
Hypertension has a complex pathogenesis and symptoms appear in advanced disease. Dysregulation of gene expression regulatory factors like microRNAs has been reported in disease development. Identifying biomarkers which could help understand the pathogenesis and prognosis of hypertension is essential. The study's objective was to investigate microRNA expression profiles according to participant blood pressure status. Next generation sequencing was used to identify microRNAs in the whole blood of 48 body mass index-, smoking- and age-matched normotensive (n = 12), screen-detected hypertensive (n = 16) and known hypertensive (n = 20) female participants. Quantitative reverse transcription polymerase chain reaction was used to validate the next generation sequencing findings in a larger, independent sample of 84 men and 179 women. Using next generation sequencing, 30 dysregulated microRNAs were identified and miR-1299 and miR-30a-5p were the most significantly differentially expressed. Both microRNAs were upregulated in known hypertensives or screen-detected hypertensives compared to the normotensives. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis indicated possible involvement of platelet activation, calcium signaling and aldosterone synthesis pathways. Further validation of miR-1299 and miR-30a-5p using quantitative reverse transcription polymerase chain reaction confirmed sequencing results while yielding new findings. These findings demonstrate microRNA dysregulation in hypertension and their expression may be related to genes and biological pathways essential for blood pressure homeostasis.